2004
DOI: 10.1007/s00438-004-1052-2
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis GNARLED gene encodes the NAP125 homolog and controls several actin-based cell shape changes

Abstract: In plants many aspects of cell shape regulation are controlled by actin-dependent processes. The ARP2/3 complex has been recognized as a regulator of actin organization. Mutations in genes encoding components of the ARP2/3 complex lead to cell shape defects in several cell types, including trichomes, epidermal pavement cells and hypocotyl cells. We show here that mutations in the GNARLED (GRL) gene cause a similar range of phenotypes. The GRL gene encodes the Arabidopsis homolog of NAP125, which in animals is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 33 publications
(58 reference statements)
0
29
0
Order By: Relevance
“…2J,K,L). This phenotype was also found in a mutant affecting ARP2-ARP3 complex function, the distorted1 mutant, and in a regulator of the ARP2-ARP3 complex, the nap1 mutant called gnarled (Brembu et al, 2004;Deeks et al, 2004;ElAssal et al, 2004a;Li et al, 2004;Zimmermann et al, 2004). The analysis of the cellular phenotype revealed that the elongation of the petiole is due to increased cell elongation of petiole cells.…”
Section: Research Articlementioning
confidence: 94%
See 2 more Smart Citations
“…2J,K,L). This phenotype was also found in a mutant affecting ARP2-ARP3 complex function, the distorted1 mutant, and in a regulator of the ARP2-ARP3 complex, the nap1 mutant called gnarled (Brembu et al, 2004;Deeks et al, 2004;ElAssal et al, 2004a;Li et al, 2004;Zimmermann et al, 2004). The analysis of the cellular phenotype revealed that the elongation of the petiole is due to increased cell elongation of petiole cells.…”
Section: Research Articlementioning
confidence: 94%
“…Normally, pavement cells form many lobes that tightly interlock to form a continuous leaf epidermal surface. ARP2-ARP3 complex mutations and mutations of ARP2-ARP3 complex regulators affect the development of leaf epidermal lobes by reducing the ability of lobes to intercalate and adhere (Basu et al, 2004;ElAssal et al, 2004a;Frank et al, 2003;Le et al, 2003;Li et al, 2004;Mathur et al, 2003a;Mathur et al, 2003b;Saedler et al, 2004a;Zimmermann et al, 2004). Tip-growing root-hair cells show reduced or wavy growth in arp2 and arpc5 mutants when root hairs are challenged to elongate rapidly (Li et al, 2003;Mathur et al, 2003b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, genetic evidence strongly supports the conclusion that this complex plays an essential role in activation of the ARP2/3 complex in Arabidopsis. 'Distorted' trichome mutants gnarled (grl) and pirogi/klunker (pir/klk), with phenotypes very similar to those of ARP2/3 complex subunit mutants, are mutations in the Arabidopsis homologs of Nap-1 and PIR121/Sra-1, respectively (El-Assal et al, 2004b;Basu et al, 2004;Deeks et al, 2004;Brembu et al, 2004;Zimmermann et al, 2004a;Li et al, 2004). In addition, dis3/itb1 mutations disrupting Arabidopsis SCAR2 produce a milder version of the same phenotype (Basu et al, 2005;Zhang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In plants small GTPases related to RHO and RAC/ CDC42 called ROPs are known and were shown to be involved in the control of actin organization (Yang, 2002;Mathur and Hulskamp, 2002;Smith, 2003). Also two of the immediate targets of ROPs, NAP125, PIR121, were identified (Basu et al, 2004;Brembu et al, 2004;Deeks et al, 2004;El-Assal et al, 2004a;Li et al, 2004;Zimmermann et al, 2004). The corresponding mutants show a similar phenotypic range as the arp2/3 mutants indicating that they are acting in the same pathway.…”
Section: Growing Straight: Trichome Expansion Is Regulated By Actinmentioning
confidence: 99%